2010
DOI: 10.1111/j.1742-6723.2009.01262.x
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral neuropathy following nitrous oxide abuse

Abstract: Undifferentiated neurological presentations are not uncommon to the ED. Vitamin B (12) deficiency can lead to progressive demyelination and axonal lesions on the peripheral nerves and cervicothoracic spinal cord causing a peripheral neuropathy. Nitrous oxide is a common adjuvant to anaesthesia in the ED but it not often thought of as a drug of abuse. A case is reported of prolonged and intensive nitrous oxide abuse that resulted in the development of a peripheral neuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 9 publications
2
21
0
1
Order By: Relevance
“…However, difference of sensory nerve impairment was not found between the lower and upper extremities. These findings were partially consistent with those of previous clinical studies performed in other countries, which reported the presence of length-dependent sensorimotor axonal neuropathy in the lower extremities of patients with nitrous oxide abuse [24][25][26].…”
Section: Discussionsupporting
confidence: 92%
“…However, difference of sensory nerve impairment was not found between the lower and upper extremities. These findings were partially consistent with those of previous clinical studies performed in other countries, which reported the presence of length-dependent sensorimotor axonal neuropathy in the lower extremities of patients with nitrous oxide abuse [24][25][26].…”
Section: Discussionsupporting
confidence: 92%
“…Lin et al 88 : Case 3 20 yo F Numbness, weakness, unsteady gait B12: #-nl; MCV: " Lunsford et al 89 29 yo M Paresthesias, weakness, unsteady gait, urinary retention B12: #; Schill I-III: # Miller et al 90 39 yo M Difficulty walking, falls B12: #; MCV: nl Morris et al 91 22 yo M Gait instability with falls B12: #; HCY: "; MMA: nl; MCV: " (Continued) 95 31 yo M Imbalance, numbness, tingling, weakness B12: #; MCV: " Prigge et al 96 31 yo F Weakness, paresthesias n/r Probasco et al 97 35 yo M Wide-based gait, paresthesias B12: #; MMA: " Pugliese et al 61 27 99 35 yo M Weakness, imbalance, urinary urgency B12: nl; MCV: nl Richardson 100 28 yo M Numbness, weakness, difficulty walking B12: #-nl; HCY: "; MCV: nl; Schill: nl Sadr 101 25 yo M Ataxia, numbness, abnormal gait B12: nl; Schill: nl Sahenk et al 102 23 yo F Numbness, unsteady gait B12: nl; MCV: nl Shulman et al 103 23 yo F Progressive limb weakness with paralysis B12: #; MCV: nl Shwe and Scelsa 104 23 yo M Paresthesias, gait unsteadiness B12: #-nl; HCY: "; MMA: "; MCV: " Sotirchos et al 105 28 yo M Weakness, numbness, paresthesias B12: #-nl; MMA: "; MCV: nl Stabler et al 106 39 yo M Paresthesias, ataxia, memory loss B12: #-nl; MCV: "; HCY: "; MMA: "; Schill I: # Stacy et al 107 54 23 yo M Numbness, paresthesias B12: #; HCY: "; MMA: "; MCV: "; Schill: nl Waters et al 111 24 yo M Numbness, tingling, incoordination, imbalance B12: #; HCY: "; MMA: "; MCV: nl…”
Section: Nitrous Oxide Abuse and Neurologic Sequelaementioning
confidence: 99%
“…Previously, reports on N 2 O toxicity have been related to GA, recreational abuse, and occupational exposure [ 49 50 51 52 53 ]. However, the important factor was not whether N 2 O was used for GA or PSA, but the degree of exposure to N 2 O: that is, the concentration of N 2 O used and how long and often the patient was exposed to N 2 O were important [ 54 55 56 ].…”
Section: Vitamin B 12 Inactivation By N mentioning
confidence: 99%